Impact of Digital Media on Political Campaigns - Thabiso Muswede (African Journal of Political Science)
This article explores the impact of digital media on political campaigns towards disintermediated political communication in Africa. It highlights that, due to the proliferation of digital media, political communication processes have drastically shifted away from traditional formats to more adaptable and personalised platforms linked to digital citizenship. It further discusses the characterisation of African political campaigns and its impact on democratisation. Application of the Adaptive structuration and Media richness theories is employed to explicate the role of information technologies in facilitating societal change. The article argues that, disintermediation in political campaigns results from unfettered access to alternative means of information with potential to diminish the power of the “voice”; stimulate new forms of political consciousness; cultivate optimisation of political engagement and yield truism through verification of political information both pre and post elections. It concludes that digital media have radically changed how the electorate participate in African politics, meanwhile cascading its ability to empower citizens to redefine their sense of political space in a disintermediated environment.